METHODS FOR ANALYZING HEAT GENERATION AND ENERGY CONSUMPTION IN VARIABLE-SPEED ASYNCHRONOUS PUMP DRIVES - Mamasidiqov Javlonbek; Dusmatov Rovshan Kamildjanovich (Modern American Journals, 2026)
Variable-speed asynchronous pump drives are widely used to improve operational flexibility and energy efficiency in modern pumping systems. However, changes in operating speed significantly affect both heat generation and energy consumption, which may influence system reliability and service life. This article analyzes methods for assessing heat generation and energy consumption in asynchronous pump drives operating under variable-speed control. The study is based on analytical evaluation of electrical and mechanical losses, thermal balance considerations, and energy performance indicators at different operating regimes. The results show that integrated analysis of thermal and energy characteristics enables identification of optimal operating conditions that minimize overheating and reduce power losses. The proposed approach supports the development of reliable and energy-efficient control strategies for variable-speed pump systems.
Keywords: Variable-speed drive; asynchronous motor; pump systems; heat generation; energy consumption